Kebijakan Tentang Raperda Jogja Smart Province Pemerintah Daerah Istimewa Yogyakarta - Aco, Faizal (Universitas Proklamasi 45, 2024)
Presidential Decree Number 20 of 2006 Information and Communication Technology (ICT)-based government management known as E-Government is using information and communication technology in government processes to increase efficiency, effectiveness, transparency, and accountability in government administration. Management of government services using ICT is implementing electronic government based on ICT to improve government performance in its relations with society, the business community, and other related groups towards good and clean governance. The research used in this research is descriptive with a qualitative approach. Meanwhile, data collection techniques use FGD techniques, observation, interviews, and documentation or literature study. Implementation of data collection methods is adjusted to the depth of information that must be explored and the availability of resources. The data taken to conduct this study consisted of primary data and secondary data. Primary data is data collected directly from the source and/or derived from direct measurements of the object of study through in-depth interviews with key figures. The research results show that the vocabulary and concept of Jogja Smart Province have been mentioned a lot, becoming a measuring point in itself. From a normative juridical perspective, the scope and concept of a smart province already have a fairly strong legal basis. Either they are originating from central government policies or from the DIY Regional Government itself. However, several things need to be added and strengthened. Conceptually, there is a need to raise the level of regulations relating to Jogja Smart Province towards the formation of regional regulation, which begins with the drafting of a regional regulation.